COVID‐19 and the shifting industrial landscape. (28th February 2021) - Gibson, Chris; Carr, Chantel; Lyons, Craig; Taksa, Lucy; Warren, Andrew
Abstract: The COVID‐19 coronavirus pandemic has fuelled debate about domestic industry and manufacturing in light of shocks to global supply chains and shortages of medical and personal protective equipment (PPE). Nevertheless, debates have been poorly attuned to geography and history. Calls for reinvigorated domestic manufacturing conceal the degree to which industrial landscapes are already entwined in geometries of power. This is especially so at ports—increasingly privatised—that have become sites of policy focus and biosecurity panic. Crucial trading zones, ports are being refashioned as growth machines for commodity export, energy, and logistics, undergirding national manufacturing capacity via trade and material commodity flows. Yet ports have also always been vectors for disease transmission and are central places for COVID‐19 crises. Writing from Port Kembla, south of Sydney, Australia, we catalogue five themes warranting geographical analysis and global comparison in light of coronavirus: disruptions to supply chains (with implications for global production networks); domestic industrial capacity and the future of manufacturing; biosecuring industrial sites; precarious labour and work; and vernacular emergency response capacities within industrial communities. Amidst heightened geopolitical tensions, geographers reveal how industrial landscapes are contested. Logistical and biosecurity roles are enveloped by enduring infrastructural materialities, local histories, and regional legacies of skill and ingenuity.